2011
DOI: 10.5713/ajas.2011.11249
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production of Different Forages in In vitro Ruminal Fermentation

Abstract: An in vitro rumen batch culture study was completed to compare effects of common grasses, leguminous shrubs and non-leguminous shrubs used for livestock grazing in Australia and Ghana on CH4 production and fermentation characteristics. Grass species included Andropodon gayanus, Brachiaria ruziziensis and Pennisetum purpureum. Leguminous shrub species included Cajanus cajan, Cratylia argentea, Gliricidia sepium, Leucaena leucocephala and Stylosanthes guianensis and non-leguminous shrub species included Annona s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
43
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 30 publications
13
43
3
8
Order By: Relevance
“…The feed ingredients were dried at 55ºC for 24h and then ground to pass a 1 mm screen and incubate in vitro (Meale et al, 2012). The entire incubation procedure was repeated twice (i.e., two incubation runs x three replicates per treatment, resulting in a total of six replicate vials per treatment).…”
Section: Methodsmentioning
confidence: 99%
“…The feed ingredients were dried at 55ºC for 24h and then ground to pass a 1 mm screen and incubate in vitro (Meale et al, 2012). The entire incubation procedure was repeated twice (i.e., two incubation runs x three replicates per treatment, resulting in a total of six replicate vials per treatment).…”
Section: Methodsmentioning
confidence: 99%
“…The relatively high IVDMD, despite the high NDF and ADF contents of Mitchell grass, implies that co-grazing camels with cattle supported a more effective microbial population in camels. Similar values of the highest cumulative gas production, IVDMD, and total VFA production were shown when in vitro rumen batch culture was completed for Brachiaria ruziziensis grass and leguminous shrub species of Gliricidia sepium that are commonly used for livestock grazing in parts of Australia and Ghana (Meale et al 2012). Meanwhile, as the subject matter by Meale et al (2012) was the evaluation of feed, it does not agree well with this present co-grazing experiment as the focus was to investigate the characteristics of FF inoculants in fermentation of feed samples.…”
Section: Volatile Fatty Acid Productionsupporting
confidence: 61%
“…Similar values of the highest cumulative gas production, IVDMD, and total VFA production were shown when in vitro rumen batch culture was completed for Brachiaria ruziziensis grass and leguminous shrub species of Gliricidia sepium that are commonly used for livestock grazing in parts of Australia and Ghana (Meale et al 2012). Meanwhile, as the subject matter by Meale et al (2012) was the evaluation of feed, it does not agree well with this present co-grazing experiment as the focus was to investigate the characteristics of FF inoculants in fermentation of feed samples. Thus, the VFA analysis performed in this present study revealed the capability of microbes in the FF rather than evaluation among pasture that was used as substrate in the in vitro fermentation study.…”
Section: Volatile Fatty Acid Productionsupporting
confidence: 61%
“…The feed ingredients were dried at 55ºC for 24 hours and then ground to paste through a 1 mm screen. Each in vitro incubation was conducted according to the methods reported by Meale, Chaves, Baah, and Mcallister (2012). The entire incubation procedure was repeated twice (i.e., two incubation runs x three replicates per treatment, resulting in a total of six replicate vials per treatment).…”
Section: In Vitro Incubationsmentioning
confidence: 99%